High-Performance Thin-Layer Chromatography-Immunostaining as a Technique for the Characterization of Whey Protein Enrichment in Edam Cheese - Mascha Treblin; Tobias von Oesen; Jana Lüneburg; Ingrid Clawin-Rädecker; Dierk Martin; Katrin Schrader; Ralf Zink; Wolfgang Hoffmann; Jan Fritsche; Sascha Rohn (Foods, 2022)
Whey protein-enriched cheese can be produced by means of a high-temperature treatment of a part of the cheese milk. In this way, the nutritional quality of the resulting cheeses can be increased while resources are conserved. High-performance thin-layer chromatography-immunostaining (HPTLC-IS) using specific β-lactoglobulin (β-LG) antibodies was applied to study the implementation and stability of β-LG in two different sample sets of whey protein-enriched Edam model cheeses, including industrial-scale ones. Two methods were compared for the extraction of the proteins/peptides from the cheese samples. By applying tryptic hydrolysis directly from a suspended cheese sample instead of a supernatant of a centrifuged suspension, a better yield was obtained for the extraction of β-LG. When applying this method, it was found that selected epitopes in the tryptic β-LG peptides remain stable over the ripening period of the cheese. For four of the tryptic β-LG peptides detected by immunostaining, the amino acid sequence was identified using MALDI-TOF-MS/MS. One of the peptides identified was the semi-tryptic peptide VYVEELKPTP. A linear relationship was found between the content of this peptide in cheese and the proportion of high-heated milk in the cheese milk. β-LG enrichment factors of 1.72 (n = 3, sample set I) and 1.33 ± 0.19 (n = 1, sample set II) were determined for the cheese samples containing 30% high-heated milk compared to the non-enriched samples. The relative β-LG contents in the cheese samples with 30% high-heated milk were calculated to be 4.35% ± 0.39% (sample set I) and 9.11% ± 0.29% (sample set II) using a one-point calibration. It can be concluded that the HPTLC-IS method used is a suitable tool for the analysis of whey protein accumulation in cheese, being therefore potentially directly applicable on an industrial scale. For more accurate quantification of the whey protein content in cheese, an enhanced calibration curve needs to be applied.